(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
There are always a number of elements in the societywhich are deprived of their basic rights in every society, state and nation,but these elements lack in the awareness of their rights. If we enlist suchelements from the society, then women would top this list. In fact, women arethe most important factor of every society. Even though everybody is aware ofthis fact, yet nobody is ready to accept this fact. As a result, the importancewhich used to be given to women is declining in today’s society. As aconsequence of this growing tendency of underestimating women such as to makethem occupy a secondary position in society and to deprive them of their basicrights, the need for empowering women was felt. Today we enjoy the benefits ofbeing citizens of a free nation, but we really need to think whether each ofthe citizens of our country is really free or enjoying freedom, in the truesense of the term. If we consider our country, each Indian citizen is givencertain basic rights. The Constitution of our nation doesn’t discriminatebetween men and women, but our society has deprived women of certain basicrights, which were bestowed upon them by our Constitution. Due to such currentsituation, it was needed to make women free from all the shackles and toempower them as well. This is nothing but empowerment of women.